AB0636 Interstitial Lung Disease in Scleroderma Portuguese Patients. (15th July 2016) - Sousa, S.I.; Duarte, A.; Cordeiro, I.; Teixeira, L.; Canas da Silva, J.; Cordeiro, A.; Santos, M.J.
Abstract : Background: Systemic sclerosis (SSc) is a rheumatic disorder characterized by inflammation and fibrosis involving the skin as well as internal organs, including the lung. Objectives: This study was conducted to characterize SSc patients with ILD and determine predictor features for the presence of ILD. Methods: A retrospective evaluation of SSc patients from our Rheumatology department was undertaken. ILD was defined according to imaging findings in high-resolution CT (HRCT) combined with functional parameters. Demographic features, auto-antibodies, spirometry, diffusion capacity for carbon monoxide (DLCO) measurement, echocardiography and 6-minute walk test were compared between groups with and without ILD using parametric tests and non-parametric tests. Predictor factors were established by logistic regression analyses. Results: One hundred and three SSc patients with current mean age of 60.2±14.1y and mean disease duration of 10.0±9.6y were evaluated. Thirty-four (35.8%) patients were diagnosed with ILD, of whom 13 had limited cutaneous SSc, 14 had diffuse cutaneous SSc, 2 sine sclerodema and 5 overlap syndroms. ANA was positive in 100% cases, anti-Scl70 was found in 55% and anti-centromere antibody positivity was found in 15% of patients. HRCT revealed diffuse parenchymal lung disease involvement >20% in 18 (53%) cases, with the majority showing a predominant honeycombing pattern. Spirometry showed a restrictive pattern in 8 patients and 1 had obstruction. The DLCOsb was abnormal in 7 patients. Three patients had pulmonary hypertension confirmed by right heart catheterization, 2 patients classified as group 1 and 3 and 1 patient of group 5. About 63% of ILD patients were ever treated with corticosteroids and 27% with cyclophosphamide, which were the most common drugs used. Two patients were also treated with rituximab. In this ILD-group, 5 deaths were recorded, 2 due to cancer, 1 abdominal sepsis, 1 pulmonary hypertension and 1 of unknown cause. Comparison of these ILD patients with non-ILD patients revealed some significantly differences (Table 1 ). Multivariate analysis showed that digital ulcers (OR=31.6, 95% CI 3.09 to 321.91), Anti-Scl70 antibody positivity (OR=10.1, 95% CI 1.19 to 85.74) and anti-centromere antibody negativity (OR=0.08, 95% CI 0.01 to 0.83) were independently associated with the presence of ILD. Conclusions: This study is one of the first studies carried out in Portugal regarding lung involvement in SSc. About one third of the patients had ILD, whose main characteristics are in accordance with other European cohorts. We confirmed that anti-SCL70 positivity, presence of digital ulcers as well as the absence of anti-centromere antibody is independently associated with ILD Disclosure of Interest: None declared